Approximation of Mixed Euler-Lagrange σ-Cubic-Quartic Functional Equation in Felbin's Type f-NLS. (12th February 2021) - Rassias, John Michael; Pasupathi, Narasimman; Saadati, Reza; de la Sen, Manuel
Abstract : In this research paper, the authors present a new mixed Euler-Lagrange σ -cubic-quartic functional equation. For this introduced mixed type functional equation, the authors obtain general solution and investigate the various stabilities related to the Ulam problem in Felbin's type of fuzzy normed linear space (f-NLS) with suitable counterexamples. This approach leads us to approximate the Euler-Lagrange σ -cubic-quartic functional equation with better estimation.